New insights into MagPI: a promising tool to determine the adhesive capacity of biofilm on the mesoscale. Issue 6 (3rd July 2018) - Gerbersdorf, Sabine Ulrike; Wieprecht, Silke; Thom, Moritz; Paterson, David M.; Scheffler, Marc
Abstract: The adhesiveness and stability of ubiquitously distributed biofilms is a significant issue in many areas such as ecology, biotechnology and medicine. The magnetic particle induction (MagPI) system allows precise determinations of biofilm adhesiveness at high temporal and spatial resolution on the mesoscale. This paper concerns several technical aspects to further improve the performance of this powerful experimental approach and enhance the range of MagPI applications. First, several electromagnets were built to demonstrate the influence of material and geometry with special regard to core remanence and magnetic strength. Secondly, the driving force to lift up the particles was evaluated and it was shown that both the magnetic field strength and the magnetic field gradient are decisive in the physics of the MagPI approach. The intricate combination of these two quantities was demonstrated with separate experiments that add permanent magnets to the MagPI system.